THE RELASIONSHIP BETWEEN INTEREST IN LEARNING WITH STUDENT LEARNING OUTCOMES ON THE MATERIAL VOLUME CALCULATIONOF FINISHING WORK IN BUILDING STONE AND CONCRATE CONSTRUCTION TECHNIQUES GRADE XI SMKN-1 PALANGKA RAYA ACADEMIC YEAR 2014/2015 - Sanupir Kalaeau; Wiratno (Jurusan Pendidikan Teknologi Dan Kejuruan, 2015)
This research is motivated by the statement that based on observation and interview which suspected that there was a problem with student interest in the subject of finishing of building in class Stone and Concrete Construction Techniques, thus adversely affects the learning outcomes of students with an average grade achieved only 55 whereas for minimum completeness criteria set is 70. The low student interest allegedly affected by many factors, some of which the subject matter is deemed less important and less useful and elusive, the attitude and the way teachers teach less gimmicky, less conducive environment or often noisy. This study aimed to determine whether there is a relationship between interest in learning with student learning outcomes in the subject matter of finishing the buildings in class XI Engineering Construction Stone and Concrete SMK 1 Palangka Raya. This study uses a quantitative approach to the type of research method of correlation which is a statistical analysis looking for a relationship variables X (interest in learning) and Y (learning outcomes). The sample in this study used a sample of saturated or all members of a population of 26 students. Data collection instruments interest using a questionnaire which refers to the Likert scale and the data collection instruments of learning outcomes using test questions. After the instruments tested and found suitable for use in collecting the data, then the data that has been collected is tested to meet the requirements analysis. Once the data is deemed eligible, the data variables X and Y are analyzed using statistical analysis Pearson Product Moment correlation. The results of the data analysis and the findings showed that students' interest in class XI Stone and Concrete Construction Technique in good condition, it is the most prominent because it is influenced by media using projector. Increased student interest also followed by the high student learning outcomes in building finishing materials, proved more students scored above the minimum completeness criteria. The results of data analysis using Pearson Product Moment correlation also showed a correlation or a positive and significant relationship between interest in learning with learning outcomes, with a correlation coefficient (rxy) of 0.482 and a correlation coefficient in the table (rtable) is equal to 0.404. Because rxy(0,482) > rtable (0,404), H0 is rejected and Ha accepted(Ha: r#0).